التنبؤ المناخي بإنتاج محصول الحنطة للفترة من (1986-2010) بأستخدام نماذج السالسل الزمنية الخطية - حسين هاله فاضل; مثنى حسيبة كامل (Al-Nahrain Journal of Science, 2018)
It is Known That One of the Most Important Processes Development of Future Plans, This requires the Adoption of Advanced Statistical Methods and the Most Important Methods of Time Series Analysis Which Takes in to Account the Temporal Changes in the Study of Phenomena. Thus it Was Randomized Study Models From Time Series stationary and Non stationary Using (Box & Jenkins) Method in the Construction of the Time Series, Starting From The Diagnostic Process and Even the Process of Putting the Right Model and Predict the Phenomenon Studied. Also Test These Models by Using (Box & Peirce) test. The Research Aims to Predict Crop Production by Using Nonlinear Time Series and reach the Best Model Can Predict by Comparison with Some of Criteria through the Application.